Detection of oral biomarkers as a diagnostic tool for orthodontically induced inflammatory root resorption: a literature review - Camarena Fonseca, Alexandra (2022)
Orthodontically induced inflammatory root resorption (OIIRR) is one of the most common complications of orthodontic treatment. Historically, only radiographic methods were available, while offering ease of use and accessibility, many limitations exist. Problems of technique, standardization, limited points of view and radiation exposure remain. Resorption can only be detected after a significant portion of the root has been lost (60% to70% mineralized tissue). Moreover, these methods are static and cannot indicate if the process of root resorption has arrested or is ongoing. Recently, oral fluids have been used as a tool for the diagnosis and monitoring of oral and systemic diseases through the detection of biomarkers. The purpose of this review is to describe the scientific evidence related to the prevalence, etiology, the traditional diagnostic methods and the advances in the detection of oral biomarkers through molecular biology for this pathology.